Direct 3D Printing of Shear‐Thinning Hydrogels into Self‐Healing Hydrogels. (15th July 2015) - Highley, Christopher B.; Rodell, Christopher B.; Burdick, Jason A.
<x xml:space="preserve">Abstract</x> Supramolecular hydrogels are used in the 3D printing of high‐resolution, multimaterial structures. The non‐covalent bonds allow the extrusion of the inks into support gels to directly write structures continuously in 3D space. This material system supports the patterning of multiple inks, cells, and void spaces.